The State, the Museum and the Ethnographer in Constructing National Heritage: Defining Estonian National Costumes in the 1930s - Marleen Nõmmela (Journal of Ethnology and Folkloristics)
In this article I attempt to analyse the way in which the Estonian national costume, as heritage, was defined through the cooperation of the state, the museum and ethnographers in the 1930s. The nationalist state wished to strengthen the national identity of Estonia. The Estonian National Museum (ENM) as a repository of memory and knowledge availed its resources to support cultural propaganda. The ethnographer Helmi Kurrik, a woman of strong will and keen interest in folk textiles, managed to fulfil her obligation at the expense of her own health. The primary result of her labours was a handbook entitled Eesti rahvarõivad (Estonian Folk Costumes) (1938) which has influenced general knowledge of folk costumes in Estonia up to the present day – the ‘right’ national costumes are believed to derive from authentic ethnographical folk costumes held in the Estonian National Museum.